NILAI-NILAI UMMATAN WASATAN UNTUK MELAWAN INTOLERAN (Studi Teks, Konteks, dan Kontekstualisasi terhadap Q.S. Al-Baqarah ayat 143) - Huzdaeni Rahmawati (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
As we know, Indonesia is an unique country with various tribe, ethnic, language, culture, and religion. All the diversity to be incorporated in the concept â€œBhineka Tunggal Ikaâ€ which means different but remains just one. This unity that makes Indonesia mre beautiful within its harmonization. However, at this moment Indonesia is going through a crisis of tolerance where every individual or group blames others individual or group. An unity is very important for Indonesiaâ€™s progress. Surely, We need a solution for intolerance problem. This paper analyze about ummatan wasathan or the middle mankind as Islamic thinking for dig up its values. By using study text, context, and contextualization towards Q.S. Al-Baqarah : 143 this paper tries to catch message, and meant from that verse. This verse mentions that Alloh has made Islam mankind to be ummatan wasathan. The conclusion from this paper is for answer intolerance problem that threatens an unity in Indonesia, so that the harmonization within various can keep to be saved, and preserved.